Analisis Break Even Point Usaha Tempe Pada Industri Albarokah di Desa Karya Abadi Kecamatan Taopa Kabupaten Parigi Moutong - Khatima, Husnul; Fitryani, Fitryani; Malik, Shintami R. (SINTA Journal (Science, Technology, and Agricultural), 2024)
An increase in the price of raw materials can cause a reduction in revenue and profits obtained by Albarokah tempe business owners. The industry also still does not carry out financial records properly so it cannot identify the exact amount of income and the amount of costs incurred. This research aims to determine the amount of income and Break Even Point value of the Albarokah tempe business in Karya Abadi Village, Taopa District, Parigi Moutong Regency. The determination of respondents was carried out purposively. The respondents in the research were 3 company leaders and workers. The data analysis used is income analysis and Break Even Point analysis. The research results show that in 2023 the amount of tempeh production will be 7,800 kg, with total costs of IDR 118,573,606 and revenues of IDR 140,400,000, resulting in tempe business income generated by the Albarokah Industry of IDR 21,826,394. The Break Even Point (BEP) unit of tempeh production produced was 2,657 kg, and the Rupiah BEP was IDR 47,826,000.